2012
DOI: 10.3109/07420528.2012.706765
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Histone H3K9 Acetylation of Clock Genes and Abnormal Glucose Metabolism in ob/ob Mice

Abstract: Recent chronobiological studies found significant correlation between lack of clock function and metabolic abnormalities. We previously showed that clock gene expressions were dampened in the peripheral tissues of obese and diabetic ob/ob mice. However, the molecular mechanism of the disturbance remained to be determined. In this study, we demonstrated for the first time that acetylation levels of histone H3 lysine 9 (H3K9) at the promoter regions of clock genes, such as Dbp, Per2, and Bmal1, in the adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…When compared to wild type mice, ob / ob mice also have intact SCN clock gene expression but abnormal peripheral clock gene expression, and these abnormalities were present prior to the onset of the metabolic phenotype 61 . It has also been shown that acetylation levels, indicative of transcriptional activation, of clock gene promoters were reduced in ob / ob mice 62 , which may partially contribute to the obese phenotype via disturbed clock function.…”
Section: Rhythms In Liver Metabolismmentioning
confidence: 99%
“…When compared to wild type mice, ob / ob mice also have intact SCN clock gene expression but abnormal peripheral clock gene expression, and these abnormalities were present prior to the onset of the metabolic phenotype 61 . It has also been shown that acetylation levels, indicative of transcriptional activation, of clock gene promoters were reduced in ob / ob mice 62 , which may partially contribute to the obese phenotype via disturbed clock function.…”
Section: Rhythms In Liver Metabolismmentioning
confidence: 99%
“…Conceivably, the repeated weight cycling may have evoked lasting epigenetic changes, which has been indicated to ensure specificity and plasticity in the regulation of circadian rhythm in response to metabolic cues (1,43). Differential histone H3K9 acetylation was identified recently in the promoter region of clock genes such as Dbp, Per2, and Bmal1 in mouse adipose tissue (22). The mechanism leading to altered clock gene expression could be related to the energy restriction periods, the subsequent regain periods, or both.…”
Section: E220mentioning
confidence: 99%
“… 18 19 Our previous studies showed that acetylation level of histone H3K9 at the promoter region of Dbp and DBP mRNA expression in epididymal adipose tissue were significantly reduced in ob/ob mice, one of the animal models of human DM2. 9 10 We also found that histone deacetylases (HDACs) inhibitors increased DBP mRNA expression and decreased blood glucose in these animals with diabetes. In healthy cells, there is a tightly controlled equilibrium between the effects of histone acetyltransferases (HATs) and HDACs enabling histone (de)acetylation and the dynamic control of gene transcription.…”
Section: Discussionmentioning
confidence: 76%
“…8 We have previously reported that the acetylation of histone H3 lysine 9 (H3K9) at the promoter regions of Dbp gene and DBP mRNA expression in mice with obesity having diabetes (ob/ob) are significantly reduced in epididymal adipose tissue. 9 Recently, we showed…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation